PENGARUH KEDISPLINAN, GAYA BELAJAR, KEMANDIRIAN BELAJAR, POLA ASUH ORANG TUA, DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA PELAJARAN EKONOMI - Latifah, Siti; Ronald, Jimi; stevani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the influence of discipline, learning style, learning independence, parenting patterns, and the school environment on the learning motivation of class X students in Economics subjects at SMAN 1 Siberut Selatan. The research uses a quantitative approach with survey methods. The research population was 232 students, and 147 students were selected as samples using probability sampling techniques. The instrument used was a closed questionnaire, while the data analysis technique was carried out through path analysis with the t test, F test, and multilevel test. The research results show that learning style, learning independence, parenting patterns, and the school environment have a significant effect on discipline. Discipline is proven to have a significant effect on learning motivation, while learning style, learning independence, and parenting patterns also have a significant effect on learning motivation. However, the school environment does not have a significant influence on learning motivation. These findings confirm that both internal and external factors play a role in influencing students' learning motivation, with discipline as an important mediating variable in increasing learning motivation.